Pengaruh Gaya Kepemimpinan dan Kompensasi Terhadap Kinerja Karyawan PT Magatti Market Indonesia - Siardin Andi Djemma; Trisna Safitri; Naida (Precise Journal of Economic, 2025)
Organizational success is highly dependent on employee performance, especially in the midst of intense business competition such as at PT Magatti Market Indonesia. This study analyzes the influence of leadership style and compensation on employee performance at PT Magatti Market Indonesia, considering the challenges faced by the courier profession. The study population was 80 employees of PT Magatti Market Indonesia (saturated sample), with data collected through questionnaires and documentation. Data analysis used multiple linear regression, t-test, F-test, coefficient of determination, and classical assumption test. The results of the study indicate that partially, leadership style has a positive and significant effect on employee performance (significance <0.05). However, compensation does not have a significant effect (significance >0.05). Simultaneously, leadership style and compensation have a significant effect on employee performance where f count 4.721> f table 3.12 and significance <0.05. The coefficient of determination is 0.109 or 10.9%, indicating that 10.9% of employee performance variation is explained by these two variables, while the rest is influenced by other factors.